Pengembangan Sistem Informasi Tracer Study Berbasis User Centered Design (UCD) Menggunakan Framework Laravel - Alvira Karisma Putri; Magdalena Ariance Ineke Pakereng (STMIK Budi Darma, 2021)
This research is entitled Implementation of the Laravel Framework in the Development of a Website-Based Tracer Study System. There are also cases that are raised in this research which is the system used is very simple and still uses Google Forms, the system is still uncomfortable because anyone can fill in the Tracer Study form and the information on the Tracer Study is only owned by the Deputy Dean. The purpose of this research is to create a website-based Tracer Study data system using the Laravel framework, which is useful for helping the SWCU FKIP in gathering Alumni information. The procedure used in this research is field research and development procedures using the User Centered Design method. To overcome this problem, the authors improve the Tracer Study system in FKIP by using a Laravel framework and creating a login as system security. The result of this research is the creation of a Tracer Study data system that can facilitate information gathering and can be accessed by Faculty Leaders and Lecturers